Preparation and properties of a new porous ceramic material used in clean energy field. Issue 7 (July 2019) - Wang, Shuming; Zhang, Xiaofang; Kuang, Fenghua; Li, Jiangshan; Wang, Yanxin; Wang, Ruiping; Wang, Yanru; Lin, Xin; Li, Jianming
Abstract: At high temperature, the oxide redox reactions of ceria can split H2 O and CO2 to produce H2 and CO, so porous ceria with high temperature resistance and high specific surface area has an important foreground in clean energy applications. In this work, a reticulated porous ceria ceramic material with interconnected porous structure was prepared by the impregnation technique using organic polyurethane sponges as template. The influences of pretreated sponge, dipping time length, pore size and sintering temperature on the porosity and strength of the porous ceria ceramics were systematically studied. With the increasing sintering temperature, the glass phase occurred and led to an increase in strength, but an decrease in porosity. Eventually, we analyzed the relationships between porosity and strength of these porous materials, aiming to provide theoretical and practical references for its application in clean-energy field.